2013
DOI: 10.1177/1541931213571398
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Performance, Workload, and Usability of a Gamepad and Joystick in a Complex Task

Abstract: Complex human system interface systems such as unmanned vehicles utilize controls that range from standard joystick and keyboard interfaces to Xbox controllers. However, few research studies have been conducted to compare Xbox controllers with other types of interfaces, showing mixed results between those controllers. The current study compared the performance of a joystick and keyboard interface with that of an Xbox controller in both a low and high difficulty task. The results indicate that the Xbox controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…The Xbox controller resulted in the fastest reticle adjustment and marker placement performance, except in the 100% transparency condition, in which mouse and Xbox were equally fast. These results agree with previous research (Rupp et al, 2013), and support the importance of interface control selection. However, there was no effect of controller on accuracy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The Xbox controller resulted in the fastest reticle adjustment and marker placement performance, except in the 100% transparency condition, in which mouse and Xbox were equally fast. These results agree with previous research (Rupp et al, 2013), and support the importance of interface control selection. However, there was no effect of controller on accuracy.…”
Section: Discussionsupporting
confidence: 93%
“…Users must mentally map joystick actions to their intentions (Rogers, Bowman, & Oliver, 2015). Some researchers have found that Xbox and joystick controllers result in better performance (Jagacinski, Hartzell, & Ward, 1978;Rupp, Oppold, & McConnell, 2013) (MacKenzie & Soukoreff, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The first category is typically combined with an element of the second one and is used in ground control stations for both military and civil applications (Haque et al, 2017). The second category, some elements of which have been also compared (Rupp et al, 2013), is very frequently used in entertainment (Kim et al, 2018). A customer-level instance of the third category involving a virtual joystick is provided by Parrot with the AR.FreeFlight 2 application interface (Parrot, 2012); a second instance regards a prototype of multitouch drone control (Kang et al, 2018).…”
Section: Related Work On Traditional and Natural Interaction-based Dr...mentioning
confidence: 99%
“…Furthermore, they can provide haptic feedback without requiring the operators to look away from the screen. Rupp et al (2013) compared the performance of an Xbox 360 gamepad to that of a joystick and keyboard to remotely control an unmanned vehicle. The results showed that the gamepad was easier to use, which was operationalised as lower error rates and lower workload, as well as higher usability scores.…”
Section: Control Inputmentioning
confidence: 99%